Impact of Patient Factors and Management Strategies on Outcomes After Transverse Posterior Cordotomy. (17th July 2020) - Qazi, Shafeen; Mau, Ted; Tibbetts, Kathleen M.
Abstract : Objectives/Hypothesis: Carbon dioxide laser transverse posterior cordotomy (TPC) aims to improve airway aperture in patients with glottic obstruction. Postoperative complications may worsen airway compromise and necessitate additional interventions. We sought to identify factors impacting outcomes after TPC. Study Design: Retrospective chart review. Methods: Medical records of patients who underwent TPC for glottic airway obstruction at a tertiary‐care medical center between 2008 and 2018 were reviewed. Demographics, comorbidities, and intra‐ and postoperative management strategies were analyzed. Results: Twenty patients who underwent TPC for glottic airway obstruction met inclusion criteria. The mean age was 57 years, and 13 patients were female. Mean follow‐up time was 442 days. Seven patients had posterior glottic stenosis, and 13 had bilateral vocal fold paralysis. Twelve patients developed postoperative complications including granuloma formation (four patients), hospital readmission for dyspnea due to glottic edema (five patients), need for revision surgery (nine patients), or failure to decannulate tracheotomy (five patients). Eight patients had an uncomplicated recovery with improved dyspnea, with two patients with tracheotomies decannulated. Patients with a history of smoking tobacco were more likely to experience complications ( P = .035). There were no significant differences in outcomes with respect to history of head and neck radiation or gastroesophageal reflux disease. Steroid injection at the surgical site and postoperative medications did not significantly impact outcomes. With respect to granuloma formation, none of the variables analyzed reached significance. Conclusions: History of tobacco use increases complication rates after TPC. Other patient comorbidities and intra‐ and postoperative management strategies do not impact outcomes. Level of Evidence: 4 Laryngoscope, 131:1066–1070, 2021